The 'pantie' tumour - Silada Kanokrungsee (2018)
© 2014 S. Karger AG, Basel. We present a case of radiation-associated angiosarcoma. A 67-year-old Thai woman was diagnosed with endometrium carcinoma stage IC and was treated with surgery and radiations. Ten years later, she presented with a gradually enlarging mass on the pubic area, in the shape of a pair of panties. Skin biopsy of lesions confirmed angiosarcoma. The diagnosis was radiation-associated angiosarcoma. She was treated with chemotherapy due to unresectable tumour. The chemotherapy was started with paclitaxel 70 mg/m2 every 2 weeks. After completing the fifth cycle of paclitaxel, the lesion was markedly decreased in size and the symptoms previously described were also completely resolved.